Platelet surface CD62P and CD63, mean platelet volume, and soluble/platelet P-selectin as indexes of platelet function in atrial fibrillation : A comparison of healthy control subjects and disease control subjects in sinus rhythm - CHOUDHURY, Anirban; CHUNG, Irene; BLANN, Andrew D; LIP, Gregory Y. H (Journal of the American College of Cardiology, 2007)
The aim of this work was to comprehensively study the role of platelets in atrial fibrillation (AF), in relation to the underlying cardiovascular diseases and type of AF, and to analyze the effect of antithrombotic treatment on different aspects of platelet activation. Platelet activation is present in nonvalvular AF, but there is debate whether this is due to AF itself and/or to underlying cardiovascular diseases. A total of 121 AF patients were compared with 65 "healthy control subjects" and 78 "disease control subjects" in sinus rhythm. Platelet activation was assessed using 4 different aspects of platelet pathophysiology: 1) platelet surface expression of CD62P (P-selectin) and CD63 (a lysosomal glycoprotein) (by flow cytometry); 2) mean platelet volume (MPV) (by flow cytometry); 3) plasma levels of soluble P-selectin (sP-selectin, enzyme-linked immunoadsorbent assay); and 4) total amount of P-selectin per platelet (pP-selectin) ("platelet lysis" assay). Both AF patients and "disease control subjects" had higher levels of CD62P (p < 0.001), CD63 (p < 0.001), and sP-selectin (p < 0.001) compared with "healthy control subjects," with no difference between AF patients and "disease control subjects." Patients with permanent AF had higher levels of sP-selectin (p = 0.014) and MPV (p = 0.025) compared with those with paroxysmal AF. The presence of AF independently affected the levels of CD62P expression, while "high-risk" AF patients (CHADS score > or =2) had higher levels of CD62P compared with those with "low risk." Introducing warfarin resulted in a reduction of pP-selectin (p = 0.013). There is a degree of excess of platelet activation in AF compared with "healthy control subjects," but no significant difference between AF patients and "disease control subjects" in sinus rhythm. Platelet activation may differ according to the subtype of AF, but this is not in excess of the underlying comorbidities that lead to AF. Platelet activation in AF may be due to underlying cardiovascular diseases, rather than due to AF per se.